2000
DOI: 10.1176/appi.ajp.157.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Suicide Attempts of Patients With Major Depressive Episode and Borderline Personality Disorder: A Comparative Study

Abstract: Comorbidity of borderline personality disorder with major depressive episode increases the number and seriousness of suicide attempts. Hopelessness and impulsive aggression independently increase the risk of suicidal behavior in patients with borderline personality disorder and in patients with major depressive episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
238
2
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(276 citation statements)
references
References 38 publications
20
238
2
16
Order By: Relevance
“…However, it is important to note that literature in this area has been inconsistent. Many other studies have found a significant relationship between hopelessness and past suicide attempt status (Soloff et al, 2000;Rifai et al, 1994;Fawcett et al, 1987;Beck et al, 1985). This inconsistency may be due to differences in methodologies such as characteristics of the sample: clinical vs. non-clinical samples or differing psychiatric diagnoses of subjects.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is important to note that literature in this area has been inconsistent. Many other studies have found a significant relationship between hopelessness and past suicide attempt status (Soloff et al, 2000;Rifai et al, 1994;Fawcett et al, 1987;Beck et al, 1985). This inconsistency may be due to differences in methodologies such as characteristics of the sample: clinical vs. non-clinical samples or differing psychiatric diagnoses of subjects.…”
Section: Discussionmentioning
confidence: 94%
“…Une recherche rĂ©alisĂ©e aux États-Unis auprĂšs d'une population clinique adulte (Soloff, Lynch, Kelly, Malone, & Mann, 2000) rĂ©vĂšle que la prĂ©valence de tentative de suicide atteignait plus de 70 % chez les participants prĂ©sentant un TPL. Ces derniers comptaient en moyenne trois tentatives de suicide antĂ©rieures au moment de leur inclusion dans l'Ă©tude.…”
Section: Conduites Suicidairesunclassified
“…Regarding reliability, we expected the four LPI scales to be internally consistent, as each subscale measures a unitary construct. Regarding validity, we expected the LPI would be moderately correlated with depression, demonstrating convergent validity; the LPI is intended to measure emotional dysregulation, which often presents with hopelessness and depression [27,28]. We also expected LPI scores to correlate moderately with suicidal ideation and suicide-related behaviors, as suicidal thinking and behavior are highly prevalent among individuals with BPD [27].…”
Section: The Lpimentioning
confidence: 99%